Immune-Enhancing Effects of Taishan Pinus massoniana Pollen Polysaccharides on DNA Vaccine Expressing Bordetella avium ompA - Zhu, Fujie; Liu, Xiao; Sun, Zhenhong; Yu, Cuilian; Liu, Liping; Yang, Shifa; Li, Bing; Wei, Kai; Zhu, Ruiliang (Frontiers in Microbiology, 2016)
Bordetella avium is the causative agent of bordetellosis, which remains to be the cause of severe losses in the turkey industry. Given the lack of vaccines that can provide good protection, developing a novel vaccine against B. avium infection is crucial. In this study, we constructed a eukaryotic expression plasmid, which expressed the outer membrane protein A (ompA) of B. avium, to prepare a B. avium recombinant ompA-DNA vaccine. Three concentrations (low, middle, and high) of Taishan Pinus massoniana pollen polysaccharides (TPPPS), a known immunomodulator, were used as adjuvants, and their immune conditioning effects on the developed DNA vaccine were examined. The pure ompA-DNA vaccine, Freund's incomplete adjuvant ompA-DNA vaccine, and the empty plasmid served as the controls. The chickens in each group were separately inoculated with these vaccines three times at 1, 7 and 14 days old. Dynamic changes in antibody production, cytokine secretion, and lymphocyte count were then determined from 7 days to 49 days after the first inoculation. Protective rates of the vaccines were also determined after the third inoculation. Results showed that the pure DNA vaccine obviously induced the production of antibodies, the secretion of cytokines, and the increase in CD4+ and CD8+ T lymphocyte counts in peripheral blood, as well as provided a protective rate of 50% to the B. avium-challenged chickens. The chickens inoculated with the TPPPS adjuvant ompA-DNA vaccine and Freund’s adjuvant ompA-DNA vaccine demonstrated higher levels of immune responses than those inoculated with pure ompA-DNA vaccine, whereas only the ompA-DNA vaccine with 200 mg/mL TPPPS completely protected the chickens against B. avium infection. These findings indicate that the B. avium ompA-DNA vaccine combined with TPPPS is a potentially effective B. avium vaccine.